Biogas production from hydrothermal liquefaction wastewater (HTLWW): Focusing on the microbial communities as revealed by high-throughput sequencing of full-length 16S rRNA genes. (1st December 2016) - Chen, Huihui; Wan, Jingjing; Chen, Kaifei; Luo, Gang; Fan, Jiajun; Clark, James; Zhang, Shicheng
Abstract: Hydrothermal liquefaction (HTL) is an emerging and promising technology for the conversion of wet biomass into bio-crude, however, little attention has been paid to the utilization of hydrothermal liquefaction wastewater (HTLWW) with high concentration of organics. The present study investigated biogas production from wastewater obtained from HTL of straw for bio-crude production, with focuses on the analysis of the microbial communities and characterization of the organics. Batch experiments showed the methane yield of HTLWW (R-HTLWW) was 184 mL/g COD, while HTLWW after petroleum ether extraction (PE-HTLWW), to extract additional bio-crude, had higher methane yield (235 mL/g COD) due to the extraction of recalcitrant organic compounds. Sequential batch experiments further demonstrated the higher methane yield of PE-HTLWW. LC-TOF-MS, HPLC and gel filtration chromatography showed organics with molecular weight (MW) < 1000 were well degraded. Results from the high-throughput sequencing of full-length 16S rRNA genes analysis showed similar microbial community compositions were obtained for the reactors fed with either R-HTLWW or PE-HTLWW. The degradation of fatty acids were related with Mesotoga infera, Syntrophomonas wolfei et al. by species level identification. However, the species related to the degradation of other compounds (e.g. phenols) were not found, which could be due to the presence of uncharacterized microorganisms. It was also found previously proposed criteria (97% and 98.65% similarity) for species identification of 16S rRNA genes were not suitable for a fraction of 16S rRNA genes. Graphical abstract: Highlights: The methane yield of HTLWW was increased after petroleum ether extraction. Organics in HTLWW with molecular weight (MW) < 1000 were well degraded. High-throughput sequencing of full-length 16S rRNA genes was applied. Microbial community compositions were analyzed down to the species level.